The external constraint to the economic growth in three blocks of the world economy - Julio Herrera; Jesus Santamaria (European Regional Science Association (ERSA), 2001)
In this paper we analyze the relationships between the economic growth and the external trade balance. We divide our work in two parts. In the first part of the paper we thinks about two models: an adjustment model via prices (neoclassical model) and an adjustment model via income (keynesian model). In this first part our start point is a discussion of the paper played by the exchange rate and the Thirwall's law. In second part we estimates by way of technical of panel data and cointegrations techniques both models. A broad sample made for the most representative countries from: European Union, Mediterrranean Countries, very external indebted PVD, and Asian Dragons.
Keywords: 330